An Item Response Theory Analysis of the Sexual Compulsivity Scale and Its Correspondence with the Hypersexual Disorder Screening Inventory among a Sample of Highly Sexually Active Gay and Bisexual Men. (15th December 2014) - Ventuneac, Ana; Rendina, H. Jonathon; Grov, Christian; Mustanski, Brian; Parsons, Jeffrey T.
Abstract Introduction Numerous scales and assessments are available to assess sexual compulsivity (SC). Aim This study sought to conduct an item response theory (IRT) analysis of the Sexual Compulsivity Scale (SCS) to provide evidence about its measurement precision at the various levels of the SC construct in a sample of highly sexually active gay and bisexual men (GBM). Methods SCS data from a sample of 202 GBM who are highly sexually active but who vary in their experiences of SC symptoms were modeled using Samejima's polytomous graded response IRT model. To describe the performance of the SCS relative to the Hypersexual Disorder Screening Inventory (HDSI), SCS scores were compared with participants' corresponding HDSI results to determine sensitivity, specificity, positive and negative predictive values, and accuracy. Main Outcome Measures This study examined the correspondence between the SCS and the HDSI, a diagnostic instrument for the screening of hypersexuality. Results IRT analyses indicated that, although two of the SCS items had low reliability, the SCS as a whole was reliable across much of the SC continuum. Scores on the SCS and the HDSI were highly correlated; however, no potential cutoffs on the SCS corresponded strongly with the polythetic scoring criteria of the HDSI. Conclusion Comparisons of SCS scores with HDSI results indicated that the SCS itself could not serve as a substitute for the HDSI and would incorrectly classify a substantial number of individuals' levels of hypersexuality. However, the SCS could be a useful screening tool to provide a preliminary screening of people at risk for meeting criteria on the HDSI. Combining the SCS and the HDSI may be an appropriate evaluation strategy in classifying GBM as negative on both (i.e., "non‐hypersexual/non‐SC"), positive on the SCS only (i.e., "at risk"), and positive on both the SCS and the HDSI (i.e., "problematic hypersexuality/SC"). Ventuneac A, Rendina HJ, Grov C, Mustanski B, and Parsons JT. An item response theory analysis of the Sexual Compulsivity Scale and its correspondence with the Hypersexual Disorder Screening Inventory among a sample of highly sexually active gay and bisexual men. J Sex Med 2015;12:481–493.